REKAYASA BUDIDAYA KEPITING BAKAU MELALUI PEMOTONGAN KAKI JALAN DALAM UPAYA PENINGKATAN PRODUKSIKEPITING SOKA (SOFT SHELL) - Istiyanto Samidjan; Diana Rachmawati (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2015)
This study aimed to determine the effect of cutting the foot of the survival, growth and the rate of mangrove  crab  molting,  to  know  the  cutting  foot  path  can  maintain  the  survival,  growth  and molting best for mud crab. This study used an experimental method with a completely randomized design (CRD) 6 treatments and 10 replications that treatment A (1 foot cutting path, B (cutting 2 feet or legs road), C (3 ft cutting path), D (cutting 4 feet or two pairs of feet road), E (cutting all roads  feet),  and  F  (without  cutting  the  foot  of  the  street).  the  material  used were 120  mangrove crab  tails  with  an  average  weight  of  100  g  / head.  Case  studies  in  the  form  of  basket  made  of plastic sheeting with the size of 30x30x20 cm by 100 basketball. the data was taken from the data of  survival,  absolute  growth,  the  daily  growth.  the  data  were  analyzed  variety,  to  determine differences among the treatments tested the effect of Dual Duncan area. While the  water quality data, the rate of molting analyzed descriptively. The results showed that cutting the leg was highly significant (P <0.01) to the absolute growth and the daily growth, but significant (P <0.05) against survival rate and molting. The highest absolute growth value E (64.48 ± 28.41g), and the highest daily growth rate in treatment E (2:08 ± 0.79%). The highest survival value was treated F (90 ± 31.62%) and the highest molting in treatment E (80 ± 42.16%). Water quality media for research on decent range for maintenance of mud crab (Scylla paramamosain).Keywords : Mud crab, cutting the foot path, growth, survival, and molting